Populations evolving towards failure: costs of adaptation under competition at the range edge of an invasive perennial plant. (3rd July 2016) - Wan, Justin S.H.; Fazlioglu, Fatih; Bonser, Stephen P.
Abstract : Background : Species undergoing range expansion adapt to novel and stressful environments at range fronts. These adaptations of the edge populations may incur fitness costs. These costs may play a crucial role in stopping range expansion before absolute physiological and evolutionary limits were reached. Costs however have proven to be elusive. These may be specifically expressed under competition. Aims : Here, we assessed the costs of adaptation in range-edge populations of an invasive plant by evaluating plant responses under competition. Methods : We grew plants from range-centre and edge populations under competition treatments in a glasshouse. We predicted that plants from the range-edge would express lower reproductive efficiency under competition compared with centre population plants, and this would indicate a potentially maladaptive response. Results : Under high competition, plants from the range-edge expressed lower reproductive efficiency relative to range-centre plants which supported our prediction. In addition, they were more heavily affected by competition. Conclusions : Adaptation to novel environments at the range-edge has incurred a cost as a potentially maladaptive response under competition, which may contribute to the formation of the range-edge. This finding suggests that these costs likely form part of the classic trade-offs involved with stress-tolerance and may have effects on range evolution.